2003
DOI: 10.1271/bbb.67.278
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Paraquat-induced Oxidative Stress in Rats by Dietary Soy Peptide

Abstract: The effect of a dietary soy protein isolate (SPI), soy peptide (PEP) and the amino acids in soy protein on paraquat (PQ)-induced oxidative stress was investigated in rats. In the first experiment, male Wistar rats were fed on experimental diets containing casein (CAS), SPI and PEP as nitrogen sources with or without 0.025% PQ. The reduced food intake and body weight gain of the rats fed with PQ was mitigated by either the SPI or PEP intake. Both SPI and PEP prevented the elevation of the serum TBARS concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 19 publications
1
33
0
1
Order By: Relevance
“…In addition to being a source of nitrogen, peptides play beneficial roles in physiological activity. For example, soy peptides, the proteolytic products of soy proteins, can reduce serum lipid levels, scavenge free radicals, and reduce oxidative stress in mammalian cells (6)(7)(8). In yeast, soy peptides improve tolerance to freeze-thaw stress, repress the formation of lipid bodies (9), and accelerate ethanol fermentation (10,11).…”
mentioning
confidence: 99%
“…In addition to being a source of nitrogen, peptides play beneficial roles in physiological activity. For example, soy peptides, the proteolytic products of soy proteins, can reduce serum lipid levels, scavenge free radicals, and reduce oxidative stress in mammalian cells (6)(7)(8). In yeast, soy peptides improve tolerance to freeze-thaw stress, repress the formation of lipid bodies (9), and accelerate ethanol fermentation (10,11).…”
mentioning
confidence: 99%
“…Moreover, it has been found that substitution of L-His by D-His in a peptide leads to reduction of the antioxidative activity, which proves that configuration of amino acids also has infl uence on antioxidant activity (Chen et al, 1996;Sarmadi and Ismail, 2010). Some researchers have found that certain amino acids exhibit higher antioxidative activity when they are incorporated in dipeptides (Alabovsky et al, 1997;Takenaka et al, 2003;Erdmann et al, 2008;Sarmadi and Ismail, 2010).…”
Section: Antioxidant Propertiesmentioning
confidence: 99%
“…Hydrolysates of soy proteins contain antioxidant peptides (Chen et al, 1998). These peptides show high activity against the peroxidation of linoleic acid, paraquat-induced oxidative stress in rats, and scavenging effects on peroxynitrite, active oxygen, and free radical species (Takenaka et al, 2003). They may therefore help prevent some free radical-related diseases.…”
Section: Antioxidant Activitymentioning
confidence: 99%